Immigration, diversity and institutions. - Roupakias, Stelios; Dimou, Spiridoula (Kyklos, 2021)
This paper examines the relationship between immigration and host countries' institutional quality, using international migration data for a sample of 130 countries over the 1990–2015 period. We employ two composite metrics of political institutions, encompassing multiple dimensions of governance. To reduce endogeneity concerns, related to immigrant settlement patterns, we employ pseudo‐gravity‐based instruments in a 2SLS setting. Overall, our findings withstand several robustness checks and suggest that immigration has a negative and statistically significant impact on the level of institutional development of the countries analyzed in this study. However, there is substantial heterogeneity, since the impact of migrants appears to be somewhat stronger in less developed host countries. Interestingly, these findings are entirely driven by migrants stemming from countries displaying low institutional development.